A formative evaluation of the SAEP non-academic bridging year programme - Mahomed, Shariefah (Institute for Monitoring and Evaluation, 2016)
This dissertation reports on a formative theory-based evaluation of the non-academic component of the Bridging Year Programme (BYP) implemented by the South African Education and Environment Project (SAEP), a Non-Governmental Organisation (NGO) working mainly in the impoverished community of Phillipi near Cape Town, South Africa. The focus of the evaluation was: (1) to extract the underlying assumptions of the non-academic component of the BYP, (2) to assess the plausibility of the underlying programme assumptions and (3) to develop an outcome monitoring framework for the non-academic component of the BYP. The Bridging Year Programme Description This programme recruits learners from poor socio-economic backgrounds who have gained a National Senior Certificate (NSC) at bachelors pass level but have not gained access to their tertiary level programmes of choice. Its aim is two-fold, (1) to assist learners to improve their NSC standard in order to gain access to their tertiary education programme of choice and (2) to provide them with personal development skills to cope with the academic and social demands of tertiary education. The assumption is that if the learners' personal development skills are enhanced their prospects of success in tertiary education and the employment market will be improved. Thus, the programme comprises an academic component and a non-academic (personal development) component. The scope of this evaluation focused specifically on the non-academic component of the BYP. Background A review of local and international bridging courses found that most students from poor socio-economic backgrounds are underprepared to cope with the social and academic workload of tertiary education, leading to high tertiary-dropout rates. A number of programme evaluations found that if students are provided with a set of non-academic (personal development) skills including planning and organising, prioritising their workload and English literacy skills, they will be better prepared to cope with the academic demands, thus improving their prospects of success at tertiary institutions.